China Risen? Studying Chinese Global Power. - Breslin, Shaun; Project Muse. (Bristol, UNITED KINGDOM Bristol University Press, 2021)
Drawing on an extensive range of Chinese-language debates and discussions, this book explains the roles of different actors and interests in Chinese international interactions, and how they influence the nature of Chinese strategies for global change.
Description based on print version record.
Keywords: Since 2000; Globalization -- China; Politics and government; China -- Foreign relations -- 21st century